2014
DOI: 10.3892/or.2014.3681
|View full text |Cite
|
Sign up to set email alerts
|

Paired related homeobox 1 is associated with the invasive properties of glioblastoma cells

Abstract: Glioblastoma is a highly proliferative and invasive tumor. Despite extensive efforts to develop treatments for glioblastoma, the currently available therapies have only limited effects. To develop novel strategies for glioblastoma treatment, it is crucial to elucidate the molecular mechanisms that promote the invasive properties of glioblastoma. In the present study, we showed that the paired related homeobox 1 (PRRX1) is associated with glioblastoma cell invasion. The depletion of PRRX1 suppressed the invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…It was initially thought to be a biomarker associated with patient survival and was believed to decrease metastasis by uncoupling EMT and stemness [48]. Recently, it was reported that up-regulated PRRX1 is closely correlated with metastasis and poor prognosis in colorectal and pancreatic cancers [49, 50] and enhances invasiveness in glioblastoma cell lines [51]. These observations are in line with our results that PRRX1 is highly co-expressed with BMI1 and TWIST1 .…”
Section: Discussionsupporting
confidence: 91%
“…It was initially thought to be a biomarker associated with patient survival and was believed to decrease metastasis by uncoupling EMT and stemness [48]. Recently, it was reported that up-regulated PRRX1 is closely correlated with metastasis and poor prognosis in colorectal and pancreatic cancers [49, 50] and enhances invasiveness in glioblastoma cell lines [51]. These observations are in line with our results that PRRX1 is highly co-expressed with BMI1 and TWIST1 .…”
Section: Discussionsupporting
confidence: 91%
“…Additional IDH1 wt super-enhancers marked by 5hmC in our dataset and implicated in GBM pathogenesis included WDR1 , TGFBI and PVT1 [ 11 , 36 , 43 , 74 ]. IDH1 mt-specific super-enhancer targets marked by 5hmC in our cohort and previously implicated in GBM pathogenesis included PDGFC , PRRX1 , LIF , A XL , and CD44 [ 14 , 18 , 31 , 50 , 55 , 63 , 71 ]. Taken together, these data demonstrated enhancer/super-enhancer targeting by 5hmC as a prominent feature in HGG, with differential targeting observed between IDH1 cohorts.…”
Section: Discussionmentioning
confidence: 92%
“…[33,34] . Also, the paired related homeobox 1 (PRRX1) was associated with glioblastoma cell invasion [35] . An improved understanding of the mechanistic insights of these effects may reveal a means to create tailored, precision treatment of several malignancies.…”
Section: String Database Defines the Functional Interaction Partners mentioning
confidence: 99%